1999
DOI: 10.1007/s10434-999-0305-z
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Pleural Lavage in Esophageal Carcinoma

Abstract: Positive cytological findings for pleural lavage fluid, using Papanicolaou and Giemsa staining, is correlated with regrowth of residual tumor and poor prognosis in esophageal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…resection of thoracic ESCC has been reported, and positive pleural lavage cytology has been recognized as a prognostic indicator of recurrence (1,3). However, esophageal carcinomas are less likely to spontaneously exfoliate into the pleural cavity because most of the thoracic esophagus is not covered directly by the pleura but by adventitia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…resection of thoracic ESCC has been reported, and positive pleural lavage cytology has been recognized as a prognostic indicator of recurrence (1,3). However, esophageal carcinomas are less likely to spontaneously exfoliate into the pleural cavity because most of the thoracic esophagus is not covered directly by the pleura but by adventitia.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of exfoliated cancer cells in the pleural cavity after resection of thoracic esophageal carcinoma has been reported (1)(2)(3)(4), and positive pleural lavage cytology before thoracic closure is recognized as a prognostic indicator of recurrence in thoracic esophageal carcinoma (1,3). Therefore, effective pleural lavage is clinically important at the time of initial surgery of thoracic esophageal carcinoma because exfoliated cancer cells may be viable and tumorigenic.…”
Section: Introductionmentioning
confidence: 99%
“…However, the benefit may also be ascribed to a wider circumferential margin clearance 12 and it may be that resection of the pleural surfaces may also have prognostic implications. For instance, it has been shown that positive cytology of pleural lavage specimens may be predictive of local recurrence 22,23 . Involvement of the pleura is certainly one of the parameters assessed when performing preoperative staging laparotomy/thoracoscopy for oesophageal cancer 24,25 .…”
Section: The Significance Of Serosal Involvementmentioning
confidence: 99%
“…Previous studies have revealed that the detection of free cancer cells using lavage cytology is useful for predicting the recurrence and prognosis of lung, gastric, pancreatic, and colorectal cancers [8][9][10][11][12][13][14][15][16][17][18][19][20]. According to recent reports [21][22][23], the positivity rate of pleural lavage cytology at the beginning of the operation is only 0-1% for esophageal cancer. By contrast, the positivity rate of pleural lavage cytology after mediastinal lymphadenectomy is 5-9%.…”
Section: Introductionmentioning
confidence: 99%